2021
DOI: 10.1002/joc.7458
|View full text |Cite
|
Sign up to set email alerts
|

Weather whiplash: Trends in rapid temperature changes in a warming climate

Abstract: Both research and media attention has shown an increasing interest in rapidly changing weather, colloquially termed “weather whiplash” events. This research examines the spatial and seasonal variability of trends in seasonally standardized short‐term temperature ranges across the globe. Trends are calculated for three different “range windows”: 7‐day ranges, 1‐day departure, and diurnal (24‐hr) temperature ranges. Results show that globally, over the 70‐year period of record 7‐ and 1‐day ranges are increasing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…The study demonstrated that globally, over the 70-year period of record 7-and 1-day ranges were increasing significantly in all seasons, while diurnal trends were only decreasing substantially only in boreal autumn. Since 1985, nevertheless, ranges at all three-time windows increased substantially (Lee, 2022). The most widespread changes were happening as substantial increases in these ranges in the Southern Ocean, Africa, and South America and in regions of coastal upwelling.…”
Section: Weather Whiplashmentioning
confidence: 99%
See 1 more Smart Citation
“…The study demonstrated that globally, over the 70-year period of record 7-and 1-day ranges were increasing significantly in all seasons, while diurnal trends were only decreasing substantially only in boreal autumn. Since 1985, nevertheless, ranges at all three-time windows increased substantially (Lee, 2022). The most widespread changes were happening as substantial increases in these ranges in the Southern Ocean, Africa, and South America and in regions of coastal upwelling.…”
Section: Weather Whiplashmentioning
confidence: 99%
“…Many people have demonstrated an increasing interest in quickly changing weather, colloquially termed "weather whiplash" events. Lee (2022) investigated the variability of trends in seasonally standardized short-term temperature ranges in the world. He measured trends for three various "range windows": 7-day ranges, 1-day departure, and diurnal (24-hr) temperature ranges.…”
Section: Weather Whiplashmentioning
confidence: 99%
“…In recent decades, global warming has exacerbated water scarcity in the Andean Altiplano. Among other impacts, we should mention the dramatic decline in the extension of tropical Andean glaciers, as described in, e.g., [1][2][3][4][5], and the rise of air temperatures [6]. It is expected that both factors will favor in the mid-term a reduction in the amount of water available for human consumption and crop irrigation [7][8][9], and will increase the water demand of crops because of the higher evapotranspiration rates [10].…”
Section: Introductionmentioning
confidence: 99%
“…In 2016 and 2017, we sought to answer whether such grazing continues to benefit native annual forbs in California's coastal prairies, particularly given the extreme drought and temperature conditions in the years preceding the study. California is already experiencing, 1) progressively more 'extreme' precipitation, wherein rainfall events occur less frequently, but in larger magnitudes; 2) increasing 'whiplash' weather, when exceptionally dry and wet periods follow one another with minimal change in net precipitation; and 3) rising temperatures [29][30][31]. Over the last few decades, California grasslands have experienced increasing temperatures and aridity [32] and a 1-in-1200-year drought from 2012-2014 [33].…”
Section: Introductionmentioning
confidence: 99%